Animação e otimização - Gomes, Olívia Sobreira (2018)
In this dissertation, we present a research that involves three major areas of Applied Mathematics, Computer Graphics (CG), Probability and Optimization. The main objective is to develop strategies of movement between adversary characters in a chase where each move will be based on the solution of an optimization problem or a probabilistic rule. The dynamics of the movement will be through the formulation and implementation of optimization problems that will govern the persecution. A theoretical presentation is presented presenting the subjects related to CG, in particular: Animation and Color; Optimization, for example: De nition of the general optimization problem and its classi cation regarding the properties of the objective function as well as the characteristics of the set of feasible solutions; Probability, is de ned probabilistic model, Random Variables, in particular, Uniform, Exponential and Normal, Mathematical expectation and Law of large Numbers.